Neither So Low Nor So Short: Wages and Heights in Bourbon Spanish America from an International Comparative Perspective - Rafael Dobado-Gonzáles; Héctor García-Montero (European Historical Economics Society (EHES), 2012)
This paper offers new quantitative evidence on living standards in Bourbon America through the study of wages and heights. Neither were wages low nor were heights short by the international standards of the period. Thus, living standards of the Spanish Americans compare favourably with those of other regions of the world, including Europe. As in many parts of the West, a trend towards deterioration of real wages is observed in Spanish America at the end of the period. Our findings suggest that the Great Divergence in living standards between Spanish America and the developed Western countries might have taken place mainly after the Independence.
Keywords: 330